COMPARISON OF OFFICE, HOME AND AMBULATORY BLOOD PRESSURE MEASUREMENT IN HYPERTENSIVE PARTICIPANTS IN THE POPULATION-BASED SWISS LONGITUDINAL COHORT STUDY (SWICOS). (June 2022) - Radovanovic, Dragana; Schoenenberger-Berzins, Renate; Muggli, Franco; Gallino, Augusto; Parati, Gianfranco; Suter, Paolo; Bianchetti, Mario; Erne, Paul; Schoenenberger, Andreas
Abstract : Objective: The 2021 guideline of the ESH states that a reliable hypertension diagnosis should not be based on office BP measurement solely, but should be confirmed with the use of home BP measurement (HBPM) or 24 h ambulatory BP measurement (ABPM). The aim of our study was to compare BP measurements obtained in the office (OBPM), at home (HBPM) and ambulatory (ABPM) in individuals with elevated OBP participating in the Swiss Longitudinal Cohort Study (SWICOS). Design and method: Participants with OBP = > 140/90mmHg were invited to assess their BP using HBPM and ABPM. The cut-off for hypertension was = > 135/85 mmHg for HBPM and = > 130/80 mmHg for ABPM. White-coat hypertension (WCH) was defined as normal HPBM or ABPM in the subgroup of participants who had OBP = > 140/90mmHg. Undertreatment was defined as hypertension in HBPM or ABPM despite antihypertensive treatment. Results: Of 72 hypertensive participating subjects with office BP = > 140/90mmHg and valid measurements of HBPM and ABPM, 39 were males (aged 62.8 ± 11.8y) and 33 were females (aged 57.4 ± 14.2y). Systolic BP measured in the office (151.7 ± 15.5 mmHg) was significantly higher than values measured using HPBM (130.0 ± 13.5 mmHg) (p < 0.001) or during ABPM (131.8 ± 14.7 mmHg) (p < 0.001). Diastolic BP was also highest in the office (89.3 ± 8.0 mmHg) and significantly different from HBPM (81.6 ± 6.6 mmHg) or ABPM (80.8 ± 11.2 mmHg) (both p < 0.001). Hypertension was confirmed with HBPM in only 21 participants (29%), and with ABPM in 41 participants (57%). Participants who had hypertension according to ABPM but not to HBPM were significantly younger (p < 0.001) and more frequently working (p < 0.001). The prevalence of WCH was 44% using HBPM and 26% using ABPM. Undertreatment was found in 13 participants (18%) using HBPM and 21 (29%) using ABPM. Conclusions: This study found highest BP for OBPM; HBPM and ABPM were significantly lower. Hypertension prevalence was lower using HBPM than using ABPM in young working participants. Potentially, HBPM might lead to underdiagnosis and undertreatment. Nevertheless, the findings of this study support the ESH recommendations of complementing office BP using HBPM or ABPM given the high prevalence of WCH and undertreatment.